Unlocking the growth potential: Harnessing the power of synbiotics to enhance cultivation of pleurotus spp. - Patil, Reshma Rohit; Aizi Nor Mazila, Ramli; Ang, Shu Xuan; Ng, Zhi Xin; Nur Izyan, Wan Azelee; Bhuyar, Prakash (Zhejiang University, 2024)
The oyster mushroom (Pleurotus spp.) is one of the most widely cultivated mushroom species globally. The present study investigated the effect of synbiotics on the growth and quality of Pleurotus ostreatus and Pleurotus pulmonarius. Different synbiotics formulations were applied by spraying mushroom samples daily and measuring their growth parameters, yield, biological efficiency, proximate composition, mineral content, total phenolic content (TPC), and diphenyl-1-picryl-hydrazyl (DPPH) radical scavenging activity. Results demonstrated that the most significant yield of oyster mushrooms was harvested from synbiotics sprayed with inulin and Lactobacillus casei (56.92 g). Likewise, the highest biological efficiency obtained with a similar synbiotic was 12.65%. Combining inulin and L. casei was the most effective method of improving the mushrooms’ growth performance and nutrient content in both samples. Furthermore, synbiotics that combined inulin and L. casei resulted in the highest TPC (20.550 mg gallic acid equivalent (GAE)/g dry extract (DE)) in white oyster mushrooms (P. ostreatus). In comparison, in grey mushroom (P. pulmonarius) the highest TPC was yielded by L. casei (1.098 mg GAE/g DE) followed by inulin and L. casei (1.079 mg GAE/g DE). The DPPH results indicated that the oyster mushroom could be an efficient antioxidant. The results revealed that applying synbiotics improved the mushrooms’ quality by increasing their antioxidant capacity with higher amounts of phenolic compounds and offering better health benefits with the increased levels of mineral elements. Together, these studies demonstrated the potential of using synbiotics as a biofertilizer, which is helpful for mushroom cultivation; therefore, it might solve the challenge of inconsistent quality mushroom growers face.